The Influence Of Health Beliefs On Preventive Actions Against Pregnancy Complications: A Health Belief Model Approach - Wida Rahma, Wida; Sundari, Sundari; Ardhianingtyas, Nisa; Frameswari, Fara; Sanjaya, Kiky Anggun (Journal of Midwifery and Reproduction, 2025)
Until now, the MMR in Indonesia has not met the set target, with a maternal mortality rate of 305 per 100,000 live births in 2015. Meanwhile, the target to be achieved is 183 per 100,000 live births by 2024 (Kemenkes RI, 2021). The data regarding maternal mortality cases in Madiun Regency, which have continued to increase in the last two years, are very worrying. The purpose of this study was to determine the perception of seriousness, barriers, vulnerability and benefits with the prevention of pregnancy complications. This research method uses correlational quantitative research, the sample amounted to 30 pregnant women. The results showed that the four variables were statistically tested and significant with a Nagelkerke R2 value of 81%, meaning that the four independent variables (perceived seriousness, perceived barriers, perceived vulnerability and perceived benefits) were able to explain the pregnancy examination by 81.5% and the remaining 18.5% was explained by other factors outside the research model. The conclusion of this study is that perceptions of seriousness, barriers, vulnerability and benefits affect the prevention of pregnancy complications.